2016
DOI: 10.1097/jom.0000000000000804
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying Among Teachers

Abstract: This paper adopts the Job Demands-Resources (JD-R) model to analyze workplace bullying among teachers. The data used for this research are obtained from the 5th European Working Conditions Survey. Given the objective of this work, a subsample of 261 education employees is collected: 48.7% of these teachers report having experienced workplace bullying (N = 127), while 51.3% indicate not considering themselves as bullied at work (N = 134). In order to test the research model and hypotheses, this study relies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Work stress was one of the most important occupational factors reported in empirical studies, and was always strongly and positively related to bullying [33,35,36,49,62]. The odds ratios varied from 1.38 [49] to 4.96 [36].…”
Section: Resultsmentioning
confidence: 99%
“…Work stress was one of the most important occupational factors reported in empirical studies, and was always strongly and positively related to bullying [33,35,36,49,62]. The odds ratios varied from 1.38 [49] to 4.96 [36].…”
Section: Resultsmentioning
confidence: 99%
“…Results from a European Working Conditions Survey showed that a total 48.7% of European teachers have experienced some form of mobbing and bullying. The survey was conducted among 261 European teachers using the Job-Demand-Resources instrument (JD-R model) (32).…”
Section: Discussionmentioning
confidence: 99%
“…Many applications of occupational stressor-strain models have treated workplace bullying as an outcome variable [24][25][26][27]. By applying the strain hypothesis within the JDC model, we first aimed to treat workplace bullying as a job demand and to analyze this stressor alongside 'traditional' job stressors of role overload and low job control.…”
Section: Introductionmentioning
confidence: 99%